BIM approach for stone pavements in Archaeological Sites: The case study of Vicolo dei Balconi of Pompeii. (January 2023) - Biancardo, S.A.; Intignano, M.; Veropalumbo, R.; Martinelli, R.; Calvanese, V.; Autelitano, F.; Garilli, E.; Giuliani, F.; Dell'Acqua, G.
Highlights: Interdisciplinarity between archeology and civil engineering aspects. A proposed methodology to apply BIM to the archaeological field with a focus on stone paved roads. Scripts in a visual programming language environment to automate operations on information stored in the model. BIM as promising tool for the purposes of archaeological conservation and protection agencies. Abstract: At present, ecological and technological transition policies encourage the improvement of efficiency of engineering processes; this is the background for new methods for the digitalization of engineering works. The methodological approach of Building Information Modeling (BIM) brings a great wave of innovation, probably destined to replace previous approaches to the designing, maintenance, and management phases. The aim of this paper is to propose a methodology to apply BIM to the archaeological field (Heritage BIM - HBIM), with a focus on stone paved roads. It addresses the case study of a stretch of stone paved road located in the Archaeological Site of Pompeii in Italy. For the development of the digital model, several BIM-based tools have been used, starting from a laser scanner-based survey, which led to a point cloud that was subsequently coordinated with certain referenced points to achieve a correct geo-referenced point cloud. The corridor design process was performed by developing a Digital Terrain Model (DTM) of the paved surface and customizing the cross-section. Meanwhile, a visual programming application based on Python language was used to enrich the usability of the model itself with further operations. As result, a tool is proposed to be used in maintenance, management and restoration projects, for archaeological assets.